2015
DOI: 10.1177/2167696815597601
|View full text |Cite
|
Sign up to set email alerts
|

Arab American Emerging Adults’ Ethnic Identity and Its Relation to Psychological Well-Being

Abstract: Despite Arab Americans’ increasing population in the United States, there is limited research concerning their psychological functioning. Ethnic identity (EI) has been found to positively predict the psychological well-being of various ethnic minority individuals. Therefore, in a sample of Arab American, emerging adult college students, we investigated how Phinney’s Multigroup EI Measure subscales (i.e., Other-Group Orientation (OGO), Affirmation & Belonging, EI Exploration, and EI Commitment) predicted co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 87 publications
(144 reference statements)
1
20
0
Order By: Relevance
“…A limited number of research studies that has examined Arab American ethnic identity suggests that ethnic identity plays a similar positive role in Arab Americans. For example, stronger ethnic identity was related to lower psychological distress and increased positive psychological functioning in a sample of Arab American emerging adults (Ahmed, Kia-Keating, & Tsai, 2011;Sheldon, Oliver, & Balaghi, 2015). Specifically, the only hitherto study that examined all three ethnic identity dimensions showed that affirmation and a sense of positive belonging to their ethnic group and higher level of exploration was related to greater sense of self-acceptance, and commitment to ethnic identity was associated with a greater sense of meaningful life in this population (Sheldon et al, 2015).…”
Section: Ethnic Identity and Well-being In Arab Americansmentioning
confidence: 92%
See 4 more Smart Citations
“…A limited number of research studies that has examined Arab American ethnic identity suggests that ethnic identity plays a similar positive role in Arab Americans. For example, stronger ethnic identity was related to lower psychological distress and increased positive psychological functioning in a sample of Arab American emerging adults (Ahmed, Kia-Keating, & Tsai, 2011;Sheldon, Oliver, & Balaghi, 2015). Specifically, the only hitherto study that examined all three ethnic identity dimensions showed that affirmation and a sense of positive belonging to their ethnic group and higher level of exploration was related to greater sense of self-acceptance, and commitment to ethnic identity was associated with a greater sense of meaningful life in this population (Sheldon et al, 2015).…”
Section: Ethnic Identity and Well-being In Arab Americansmentioning
confidence: 92%
“…), self-esteem, and satisfaction with life (Diener et al, 2009). They have been used as indicators of well-being in other ethnic studies, which allows for comparison of the current study results with the existing literature on other ethnic minority groups (Sheldon et al, 2015;Umaña-Taylor et al, 2004).…”
Section: Current Studymentioning
confidence: 98%
See 3 more Smart Citations